FACTORES QUE INFLUYEN A LA EJECUCIÓN DE ACTOS DE VIOLENCIA INTRAFAMILIAR EN LA CIUDAD DE LOJA. - Sánchez Sánchez, Francel Omar (2024)
This degree work focused on knowing legal aspects that interfere with the recurrence of domestic violence. Thus, to address specific topics, a qualitative approach was used which involves inductive, analytical, descriptive, exegetical methods, as well as the application of theoretical documentary collection and interview techniques. Within the theory related to domestic violence in Loja city, these events have increased over time, creating unstable homes due to the conflictive relationships established by their members, this social phenomenon that exists generally in societies, leads to a deep analysis focused on determining the main causes that produce it, as well as having the necessary tools to stop or mitigate this problem, guaranteeing at all times the rights of the victims who have often been suffered abuse more than once by the same aggressor. When addressing the role played by justice entities in cases of domestic violence, it has been possible to identify legal factors that make it possible for this type of actions to become repeat offenders, among which we can mention the lack of speed in the processes, the sentences or resolutions issued by judges do not allow the adequate protection to the victim, and revictimization due to not having trained professional personnel when providing support to the victim.